Washington's farewell : the founding father's warning to future generations - Avlon, John P. (Simon & Schuster, 2017)
"The Farewell was published at the end of Washington's second term. It was reprinted in newspapers across the country. The President began the letter during his first term intending to retire but was persuaded by Hamilton and Jefferson to run for a second. By the end of that term he was the object of scurrilous press attacks and alarmed by the growing partisan bitterness. Fearful for the country's future, Washington pled with his countrymen to resist hyper-partisanship and foreign alliances. He called forunity among "citizens by birth or choice," defended religious pluralism, called for national education. His message to the country was urgent. Avlon describes how it was quoted by Jackson, Webster, Clay, Calhoun, and importantly by Lincoln in defense of the Union. Theodore Roosevelt and Woodrow Wilson called on it for nation-building; Kennedy for Cold war; Reagan for religion. Clinton kept a copy on his Oval Office wall. In Washington's Farewell, Avlon offers important insight into Washington's his final public days, presenting not only a startling description of the perilous state of the new nation but a rare view of the man behind the usual face of a tranquil First Father"--